Ovarian cancer - Valdivia Ponce, Eduardo (2015)
The author has studied 90 patients with cancer of the ovary at the Instituto Nacional de Enfermedades Neoplásicas, Lima from 1953-62; the overall age of the women was 47 years, and the histological classification as follows: 48.4% were serous carcinoma, 12.1 were pseudomucinous and 31.8 adenocarcinomas. The treatment in most of the cases was surgical plus roentgen therapy and chemotherapy with Thiotepa and chlorambucil; the overall survival rate was 19%. The authors remarks that the effect of radioactive gold is limited to control of the ascites, and that the cancer of the ovary is the most difficult type of neoplasm of the female tract.